The Evolution of Enterprise Reform in Africa : From State-Owned Enterprises to Private Participation in Infrastructure—and Back? - World Bank (Washington, DC, 2012)
From the outset state-owned enterprises (SOE) financial and economic performance generally failed to meet the expectations of their creators and funders. There were African SOEs that performed, at least for a time, adequately and sometimes very well, by the most stringent of standards (e.g., Ethiopian Airlines, the Kenya Tea Development Authority, Sierra Leone's Guma Valley Water Company). But the good performers were heavily outnumbered by the bad. Numerous studies and reports from this period document the poor technical and financial performance of African SOEs in general and infrastructure SOEs in particular. Many of the latter failed to produce a sufficient quantity or a high quality of service or product, and posed increasing financial burdens on strained state budgets.